Niemiecki system ubezpieczeń chorobowych - Lehmann-Knapp, Jolanta (Wydział Prawa i Administracji UAM, 1995)
The German system of sickness insurance is a reliable system which has been functioning efficiently for a number of years. For that reason, the main elements of that system have been presented in the paper. The paper is divided into three chapters. In the first one a general characteristics of the social benefits system in Germany is presented. That system has been divided into three sub-systems: social protection (prudence), social compensations and social support. Each of those has been discussed and their main objectives identified. The second chapter is devoted to statutoiy, or state sickness insurance in Germany. That system covers the majority of the population and therefore it has been given the most attention in the paper. Groups of insured parties covered by that system are presented, different types of patients insurance offices and their financing is discussed, and their relations with other elements of the social security system identified. Types of benefits payable to the insured parties within the scheme of statutory sickness insurance have also been described. The third chapter is devoted to private sickness insurance which covers a significantly smaller proportion of the more wealthy German population. In that chapter the conditions in which a change from statutory insurance schemes to private insurance systems took place are described. Methods by which insurance premium is calculated and types of benefits payable under private insurance are also presented. The last, fourth chapter, identifies the main issues related to the sickness insurance system in Germany.
German system of sickness insurance